Climate decision making: influence of prevailing social norms and probability of climate change - Choudhary, Gitanshu; Sihag, Danish; Dutt, Varun (Frontiers in Earth Science, 2024)
IntroductionThe global rise in climatic calamities necessitates effective strategies for understanding and addressing Earth’s climate complexities. Although recent research underscores simulation tools’ effectiveness in elucidating complex concepts related to Earth’s climate, partner influence on climatic decisions within simulation studies has been overlooked.MethodsEmploying the Partner Interactive Climate Change Simulator (P-ICCS), we examined 180 participants across varied conditions. The study manipulated partner nature (optimal, irrational, or none) and climate change probability (high or low) to observe effects on participants’ responses (mitigation or adaptation) within P-ICCS.ResultsResults revealed a significant impact of partner presence, with the optimal partner notably enhancing monetary investments against climate change compared to the irrational partner. Intriguingly, climate change probability did not sway participants’ investment behavior.DiscussionThe findings emphasize the pivotal role of partner influence in climate decision-making, offering insights for effective mitigation and adaptation strategies.